The Impact of the Severity of Hearing and Visual Impairment on Daily Life Experiences and the Need for Support from Others: An Interview Study - Satu Turunen-Taheri; Annica Hagerman Sirelius; Sten Hellström; Åsa Skjönsberg; Gunnel Backenroth (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
Objectives: A dual sensory loss affects communicative situations and everyday functioning and increases the risk of social isolation. The purpose of the present study was to describe experiences of disabilities and factors affecting daily life from the perspective of adult persons with severe-to-profound hearing impairment in combination with severe vision impairment. Furthermore, the study also investigated which kind of support individuals with dual sensory loss received, and their experiences as citizens in the society. Methods: The recruitment of patients with dual sensory loss was performed from 2018 to 2019 in consecutive patients at Karolinska University Hospital and at Sabbatsbergs Hospital, Stockholm, Sweden. The inclusion criteria were severe-to-profound hearing loss at 61 dB HL or more in the best ear in combination with severe vision impairment. Face-to-face interviews were conducted using a semi-structured interview guide. Semi-structured qualitative interviews were performed, analyzed, and categorized using content analysis. Results: Fourteen interviews were performed, with an equal number of participants from both sexes. Mean age of the participants was 70.1 years (47–81 years). Analysis of the data resulted in 22 categories, six sub-themes and two main themes. Examples of some of the 22 categories that were identified: Different kind of Networks, Combination’s effects, Possibilities and Limitations, Technical tools, Companion service, and Strategies. Two main themes emerged as Isolation and The Ability to control one’s own daily life. Surprisingly, most of the participants did not think of their vision and hearing impairment as a combined disability. The interviews showed various kinds of strategies to handle daily life. The Deaf-blind–team unit was reported to offer excellent health care. Companion services for persons with disabilities proved to have become more difficult to get support from and created a lack of independence and control over their own lives. However, it was also obvious that the participants felt a positive outlook on life and were more solution-oriented in order to adjust their everyday life to their life-situation. Conclusions: The combination of vision and hearing impairment demonstrated isolation, and the respondents in the study have a need for support in everyday life. At the same time, they struggle to have the ability to control their own lives. The study recommended that an individual with a combined hearing and vision impairment should immediately alert health care as these patients belong to an extremely vulnerable group. In the future, community-organized companion services should be investigated and reviewed to meet the needs of this patient group.